Concentrations and geographical variations of selected toxic elements in meat from semi-domesticated reindeer (Rangifer tarandus tarandus L.) in Mid- and Northern Norway : evaluation of risk assessment - Hassan, Ammar Ali; Brustad, Magritt; Sandanger, Torkjel Manning (International Journal of Environmental Research and Public Health, 2012)
Meat samples (n = 100) from semi-domesticated reindeer (Rangifer tarandus tarandus L.) were randomly collected from 10 grazing districts distributed over four Norwegian counties in 2008 and 2009. The main aim was to study concentrations and geographical variations in selected toxic elements; cadmium (Cd), lead (Pb), arsenic (As), copper (Cu), nickel (Ni) and vanadium (V) in order to assess the risk associated with reindeer meat consumption. Sample solutions were analysed using an inductively coupled plasma high resolution mass spectrometer (ICP-HRMS), whereas analysis of variance (ANOVA) was used for statistical analyses. Geographical variations in element concentrations were revealed, with As and Cd demonstrating the largest geographical differences. No clear geographical gradient was observed except for the east-west downward gradient for As. The As concentrations were highest in the vicinity of the Russian border, and only Cd was shown to increase with age (p < 0.05). Sex had no significant effect on the concentration of the studied elements. The concentrations of all the studied elements in reindeer meat were generally low and considerably below the maximum levels (ML) available for toxic elements set by the European Commission (EC). Thus, reindeer meat is not likely to be a significant contributor to the human body burden of toxic elements.